Prognostic Factors of Survival for High-Grade Neuroendocrine Neoplasia of the Bladder: A SEER Database Analysis - Veronica Mollica; Francesco Massari; Elisa Andrini; Matteo Rosellini; Andrea Marchetti; Giacomo Nuvola; Elisa Tassinari; Giuseppe Lamberti; Davide Campana (Current Oncology, 2022)
Background: High-grade neuroendocrine carcinoma (NEC) is a rare and aggressive variant of bladder cancer. Considering its rarity, its therapeutic management is challenging and not standardized. Methods: We analyzed data extracted from the Surveillance, Epidemiology, and End Results (SEER) registry to evaluate prognostic factors for high-grade NEC of the bladder. Results: We extracted data on 1134 patients: 77.6% were small cell NEC, 14.6% were NEC, 5.5% were mixed neuro-endocrine non-neuroendocrine neoplasia, and 2.3% were large cell NEC. The stage at diagnosis was localized for 45% of patients, lymph nodal disease (N+M0) for 9.2% of patients, and metastatic disease for 26.1% of patients. The median overall survival (OS) was 12 months. Multivariate analysis detected that factors associated with worse OS were age being >72 years old (HR 1.94), lymph nodal involvement (HR 2.01), metastatic disease (HR 2.04), and the size of the primary tumor being >44.5 mm (HR 1.80). In the N0M0 populations, the size of the primary tumor being <44.5 mm, age being <72 years old, and major surgery were independently associated with a lower risk of death. In the N+M0 group, the size of the primary lesion was the only factor to retain an association with OS. Conclusions: Our SEER database analysis evidenced prognostic factors for high-grade NEC of the bladder that are of pivotal relevance to guide treatment and the decision-making process.